Sport as a vehicle for socio-educational transformation: a study of the Fernanda Keller Project - Manuella Lopardi Steigleder; Roberto Ferreira dos Santos; Carlos Alberto Figueiredo da Silva
Abstract Aims: The aim is to identify the representations of the main actors involved in the Fernanda Keller Project on the internal and external environments of the organization. Methods: Data were collected through observation, in-depth interviews, semi-structured interviews and focus groups. Results: Findings points to the great difficulty of the interaction between the Project and the city hall, from a certain moment. In the internal environment, stand out the value attributed to the Project in the social transformation of young people, community, and professionals directly or indirectly involved in the actions. Conclusion: The project has achieved success and social impact. However, the participation of the city hall of Niterói has diminished with the passage of time. Despite the difficulties encountered, the project has found new partners in the private sector. The initiative to seek other means to obtain resources was fundamental to the project's maintenance. This posture has led everyone to a positive and involving message that permeates all the reports that this study analyzed.